Improving CAS Capabilities: New Rules for Computing Improper Integrals - Galán-García, José Luis; Aguilera-Venegas, Gabriel; Rodríguez-Cielos, Pedro; Galán-García, María Ángeles; Padilla-Domínguez, Yolanda Carmen; Atencia-McKillop, Iván; Rodríguez, Ricardo (My University, 2016)
There are diferent applications in Engineering that require to compute improper integrals of the first kind (integrals defined on an unbounded domain) such as: the work required to move an object from the surface of the earth to in nity (Kynetic Energy), the electric potential created by a charged sphere, the probability density function or the cumulative distribution function in Probability Theory, the values of the Gamma Functions(wich useful to compute the Beta Function used to compute trigonometrical integrals), Laplace and Fourier Transforms (very useful, for example in Differential Equations).
Keywords: Ecuaciones integrales